The Relationship Between Nurses’ Roles and Mothers’ Knowledge with the Implementation of HIV/AIDS Testing in the PMTCT Program among Pregnant Women at Public Health Centers in Banda Aceh City - Halizasia, Gadis; Rahmisyah, Rahmisyah; Fitria, Fitria; Riasnyah, Ferdi; Hayani, Mela; Maulida, Maulida (Jurnal Ragam Pengabdian, 2026)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system and may progress to Acquired Immunodeficiency Syndrome(AIDS). Prevention of mother-to-child transmission of HIV can be achieved through the Prevention of Mother-to-Child Transmission (PMTCT) program, including HIV testing among pregnant women. The success of HIV testing implementation is influenced by healthcare providers’ roles and maternal knowledge. This study aimed to determine the relationship between healthcare providers’ roles and maternal knowledge with the implementation of HIV/AIDS testing in the PMTCT program among pregnant women at Baiturrahman Public Health Center, Banda Aceh City. This study used an analytic observational design with a cross-sectional approach. The research was conducted in July 2024 with a sample of 44 pregnant women selected using accidental sampling. Data were collected using questionnaires and analyzed using univariate and bivariate analysis with the Chi-Square test at a significance level of α = 0.05. The results showed that most respondents perceived healthcare providers as having an active role (33 respondents; 75%), had good knowledge (26 respondents; 59.1%), and accepted HIV/AIDS testing (36 respondents; 81.8%). The Chi-Square test revealed a significant relationship between healthcare providers’ roles and HIV/AIDS testing implementation (p = 0.001), as well as between maternal knowledge and HIV/AIDS testing implementation (p = 0.000). It can be concluded that healthcare providers’ roles and maternal knowledge are significantly associated with HIV/AIDS testing implementation in the PMTCT program. Strengthening education, counseling, and health promotion by healthcare providers is needed to improve HIV testing coverage and prevent mother-to-child HIV transmission.